Neutral zone recording in computer‐guided implant prosthesis: A new digital neuromuscular approach - Massimo Frascaria; Davide Pietropaoli; Matteo Casinelli; Ruggero Cattaneo; Eleonora Ortu; Annalisa Monaco (Clinical and Experimental Dental Research, 2019)
Abstract Background Neutral zone (NZ) is a specific area in the oral cavity where muscular opposite forces are null. NZ represents the ideal zone for prosthesis placement. In this study, we compared digital implant planning using conventional technique and using NZ registration through piezography. Methods Sixty‐tree implants were digitally planned. Angular deviation differences between traditional planned and NZ‐planned implants were calculated. In addition, interferences with soft tissues (i.e., tongue and cheeks) were evaluated. Results We observed a significant difference between traditional technique and piezographic approach in terms of implants angulation (p = .003), independent of site. A 4.7% of the planned abutments with traditional technique were placed outside the NZ, causing conflict with soft tissues in the digital model. Conclusions Compared with traditional technique, piezography allows a significantly different exploitation of the nonconflict area, which potentially translates into better management of soft tissues and improved functionality of the implants.